Reindeer Husbandry and Global Environmental Change Pastoralism in Fennoscandia - Horstkotte, Tim; Holand, Øystein; Kumpula, Jouko; Moen, Jon (Earthscan Studies in Natural Resource Management, 2022)
This volume offers a holistic understanding of the environmental and societal challenges that affect reindeer husbandry in Fennoscandia today. Reindeer husbandry is a livelihood with a long traditional heritage and cultural importance. Like many other pastoral societies, reindeer herders are confronted with significant challenges. Covering Norway, Sweden and Finland - three countries with many differences and similarities - this volume examines how reindeer husbandry is affected by and responds to global environmental change and resource extraction in boreal and arctic social-ecological systems. Beginning with an historical overview of reindeer husbandry, the volume analyses the realities of the present from different perspectives and disciplines. Genetics, behavioural ecology of reindeer, other forms of land use, pastoralists' norms and knowledge, bio-economy and governance structures all set the stage for the complex internal and externally imposed dynamics within reindeer husbandry. In-depth analyses are devoted to particularly urgent challenges, such as land-use conflicts, climate change and predation, identified as having a high potential to shape the future pathways of the pastoral identity and productivity. These futures, with their risks and opportunities, are explored in the final section, offering a synthesis of the comparative approach between the three countries that runs as a recurring theme through the book. With its richness and depth, this volume contributes significantly to the understanding of the substantial impacts on pastoralist communities in northernmost Europe today, while highlighting viable pathways to maintaining reindeer husbandry for the future. This book will be of great interest to students and scholars of both the natural and social sciences who work on natural resource management, global environmental change, pastoralism, ecology, social-ecological systems, rangeland management and Indigenous studies.